Causal association between psoriasis vulgaris and bullous pemphigoid: a two-sample bidirectional Mendelian randomization study - Aobei Zhang; Aobei Zhang; Aobei Zhang; Aobei Zhang; Zhihui Yang; Zhihui Yang; Zhihui Yang; Zhihui Yang; Tao Huang; Tao Huang; Tao Huang; Mingyue Wang; et al. (Frontiers in Immunology, 2024)
BackgroundThe association between psoriasis vulgaris and bullous pemphigoid (BP) remains largely unknown.ObjectivesTo investigate whether there is a causal effect between psoriasis vulgaris and BP.MethodsTwo-sample bidirectional Mendelian randomization (MR) analyses were conducted using publicly released genome-wide association studies (GWAS) summary statistics. The GWAS summary statistics for BP were downloaded online from FinnGen Biobank Documentation of the R12 release, which includes 219 BP cases and 218,066 controls. The GWAS data for psoriasis vulgaris were extracted from Sakaue et al., which comprises 5072 cases and 478,102 controls. Single-nucleotide polymorphisms (SNPs) associated with exposure were selected as instrumental variables by performing additional quality control steps. The inverse-variance-weighted (IVW) method was used for the primary MR analyses, and the MR-Egger regression, weighted mode method, weighted median method, and simple mode were employed for sensitivity analyses. The MR-Egger intercept test and “leave-one-out” sensitivity analysis were performed to evaluate the horizontal pleiotropy and the potentially influential SNPs, respectively.ResultsGenetically determined log odds of psoriasis vulgaris were associated with an increased risk of BP (IVW: odds ratio (OR) = 1.263, 95% confidence interval (CI): 1.013-1.575, P=0.038). Sensitivity analyses by the weighted mode (OR=1.255, 95%CI: 0.973-1.618, P=0.106), MR Egger (OR=1.315, 95%CI: 0.951-1.817, P=0.126), simple mode (OR=1.414, 95%CI: 0.823-2.429, P=0.234) and weighted median method (OR=1.177, 95%CI: 0.889-1.559, P=0.254) derived directionally consistent relationship between the genetically predicted log odds of psoriasis vulgaris and risks of developing BP. On the contrary, we found that genetically predicted BP had no significant effect on psoriasis vulgaris (IVW: OR=0.996, P= 0.707), indicating the unidirectionality of the relationship. MR-Egger intercept tests showed no evidence of horizontal pleiotropy. No influential SNP driving the results was detected by the leave-one-out sensitivity analysis.ConclusionsOur results suggested that psoriasis vulgaris causally increases the risk of BP, highlighting the need for potential strategies for the prevention and early diagnosis of comorbid BP in patients with psoriasis vulgaris. Further researches into this association and underlying mechanisms are warranted.